Management of the Tahadduts Program to Improve Speaking Skills for UMY Students - Wahyuni, Sri; Prasetya Utama, Panji; Rahmadani, Rahmadani; Abror Wicaksono, Meidias; Ridwan (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
This study aims to describe the management of the Tahadduts program in improving speaking skills for UMY students. This research method uses a descriptive qualitative approach with research subjects including 95 UMY students who participated in the Tahadduts program. The data collection techniques were through observation, interviews, documentation, and questionnaires, which were then analyzed using interactive qualitative analysis from Miles and Huberman, which consisted of three steps: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Tahadduts program is run by implementing a management system that includes: 1) planning, including coordination meetings and classification of student and educator classes; 2) organizing, involving class divisions adjusted to class levels, namely beginners, intermediate, and advanced; 3) implementation of learning activities every Wednesday and Saturday; and 4) evaluation at the end of each month in the form of final semester exams and language level increases. In addition, the Tahadduts program has a positive impact on improving the speaking skills of UMY students, with an average questionnaire calculation result of 74.57%. Abstrak Penelitian ini bertujuan untuk mendeskripsikan manajemen program Tahadduts dalam meningkatkan keterampilan berbicara bagi mahasiswa UMY. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif dengan subyek penelitian meliputi 95 mahasiswa UMY yang mengikuti program tahaddust. Adapun teknik pengumpulan data melalui observasi, wawancara, dokumentasi dan angket, yang selanjutnya dianalisis dengan analisis kualitatif interaktif dari Miles dan Huberman yang terdiri dari 3 langkah, yaitu reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa program tahadduts dijalankan dengan menerapkan sistem manajemen yang meliputi: 1) perencanaan meliputi rapat koordinasi, klasifikasi kelas peserta didik dan tenaga pendidik, 2) pengorganisasian melibatkan pembagian kelas yang disesuaikan dengan tingkatan kelas yaitu pemula, menengah, dan lanjutan, 3) pelaksanaan kegiatan pembelajaran setiap hari Rabu dan Sabtu, dan 4) evaluasi setiap akhir bulan berupa ujian akhir semester dan kenaikan level bahasa. Selain itu, program tahadduts memberikan dampak yang positif terhadap peningkatan keterampilan berbicara mahasiswa UNY, dengan rata-rata hasil perhitungan angket sebesar 74,57%.